A mechanistic model of the cysteine synthase complex - Feldman-Salit, Anna; Wirtz, Markus; Hell, Rüdiger; Wade, Rebecca C. (Journal of molecular biology, 2009)
Plants and bacteria assimilate and incorporate inorganic sulfur into organic compounds such as the amino acid cysteine. Cysteine biosynthesis involves a bienzyme complex, the cysteine synthase (CS) complex. The CS complex is composed of the enzymes serine acetyl transferase (SAT) and O-acetyl-serine-(thiol)-lyase (OAS-TL). Although it is experimentally known that formation of the CS complex influences cysteine production, the exact biological function of the CS complex, the mechanism of reciprocal regulation of the constituent enzymes and the structure of the complex are still poorly understood. Here, we used docking techniques to construct a model of the CS complex from mitochondrial Arabidopsis thaliana. The three-dimensional structures of the enzymes were modeled by comparative techniques. The C-termini of SAT, missing in the template structures but crucial for CS formation, were modeled de novo. Diffusional encounter complexes of SAT and OAS-TL were generated by rigid-body Brownian dynamics simulation. By incorporating experimental constraints during Brownian dynamics simulation, we identified complexes consistent with experiments. Selected encounter complexes were refined by molecular dynamics simulation to generate structures of bound complexes. We found that although a stoichiometric ratio of six OAS-TL dimers to one SAT hexamer in the CS complex is geometrically possible, binding energy calculations suggest that, consistent with experiments, a ratio of only two OAS-TL dimers to one SAT hexamer is more likely. Computational mutagenesis of residues in OAS-TL that are experimentally significant for CS formation hindered the association of the enzymes due to a less-favorable electrostatic binding free energy. Since the enzymes from A. thaliana were expressed in Escherichia coli, the cross-species binding of SAT and OAS-TL from E. coli and A. thaliana was explored. The results showed that reduced cysteine production might be due to a cross-binding of A. thaliana OAS-TL with E. coli SAT. The proposed models of the enzymes and their complexes provide mechanistic insights into CS complexation.
Gesehen am 16.05.2017
Available online: 5 September 2008